Multicentre, randomised, single-blind, parallel group trial to compare the effectiveness of a Holter for Parkinson’s symptoms against other clinical monitoring methods: study protocol - Juan Carlos Martinez-Castrillo; Maria Alvarez; Dolores Vilas; Ernest Balaguer; Ignacio Alvarez; Jon Infante; Silvia Jesús; Marina Mata; Pablo Mir; Pau Pastor; María Sierra; Lydia Vela; et al. (BMJ Open)
Introduction In recent years, multiple studies have aimed to develop and validate portable technological devices capable of monitoring the motor complications of Parkinson’s disease patients (Parkinson’s Holter). The effectiveness of these monitoring devices for improving clinical control is not known.Methods and analysis This is a single-blind, cluster-randomised controlled clinical trial. Neurologists from Spanish health centres will be randomly assigned to one of three study arms (1:1:1): (a) therapeutic adjustment using information from a Parkinson’s Holter that will be worn by their patients for 7 days, (b) therapeutic adjustment using information from a diary of motor fluctuations that will be completed by their patients for 7 days and (c) therapeutic adjustment using clinical information collected during consultation. It is expected that 162 consecutive patients will be included over a period of 6 months.The primary outcome is the efficiency of the Parkinson’s Holter compared with traditional clinical practice in terms of Off time reduction with respect to the baseline (recorded through a diary of motor fluctuations, which will be completed by all patients). As secondary outcomes, changes in variables related to other motor complications (dyskinesia and freezing of gait), quality of life, autonomy in activities of daily living, adherence to the monitoring system and number of doctor–patient contacts will be analysed. The noninferiority of the Parkinson’s Holter against the diary of motor fluctuations in terms of Off time reduction will be studied as the exploratory objective.Ethics and dissemination approval for this study has been obtained from the Hospital Universitari de Bellvitge Ethics Committee. The results of this study will inform the practical utility of the objective information provided by a Parkinson’s Holter and, therefore, the convenience of adopting this technology in clinical practice and in future clinical trials. We expect public dissemination of the results in 2022.Trial registration NCT04176302; https://clinicaltrials.gov/show/NCT04176302